The effect of lyophilization and storage time on the survival rate and hydrolytic activity of Trichoderma strains - Grzegorczyk, Monika; Kancelista, Anna; Łaba, Wojciech; Piegza, Michał; Witkowska, Danuta (Folia microbiologica, 2018)
The study evaluates the survivability and storage stability of seven Trichoderma strains belonging to the species: T. harzianum (1), T. atroviride (4), and T. virens (2) after the lyophilization of their solid state cultures on wheat straw. Biomass of Trichoderma strains was freeze-dried with and without the addition of maltodextrin. Furthermore, in order to determine the ability of tested Trichoderma strains to preserve selected technological features, the biosynthesis of extracellular hydrolases (cellulases, xylanases, and polygalacturonases) after a 3-month storage of lyophilizates was investigated. Strains of T. atroviride (except TRS40) and T. harzianum TRS85 showed the highest viability after lyophilization process (up to 100%). After 3 months of storage, T. atroviride TRS14 exhibited the highest stability (95.23%); however, the number of active conidia remained at high level of 106-107 cfu/g for all tested T. atroviride strains and T. harzianum TRS85. Interestingly, after a 3-month storage of lyophilized formulations, most of the tested Trichoderma strains exhibited higher cellulolytic and xylanolytic activities compared to the control, i.e., before freeze-drying process. The highest activities of these enzymes exhibited the following: T. atroviride TRS14-2.37 U/g and T. atroviride TRS25-21.47 U/g, respectively, whereas pectinolytic activity was weak for all tested strains, with the highest value of 0.64 U/g registered for T. virens TRS109.
Keywords: Trichoderma; fermentace; mikrobiální viabilita; Spores, Fungal; lyofilizace; pšenice; Microbial Viability; biomasa; časové faktory; spory hub; hydrolasy; skladování léků; Fermentation; Hydrolases; Triticum; Drug Storage; Biomass; Time Factors; Freeze Drying